Impacts of Damming on Ichthyo-faunal Diversity of Marshyangdi River in Lamjung district, Nepal (Our Nature, 2014)
A study was conducted to assess the impacts of dam on fish diversity of Marshyangdi River and its tributaries in Lamjung district. Twenty six species of fishes belonging to 5 orders, 6 families and 18 genera were recorded from the different localities. Cyprinidae was the most dominant among the families represented by 53.8% species followed by Cobitidae (23.0%), Sisoridae (7.7%) and Channidae (7.7%) while Anguillidae and Synbranchidae accounted each by 3.9% only. Gut contents of fish species recorded were studied. Site specific presence of fish species indicated that damming on the main river affected the movement of migratory fishes. DOI: http://dx.doi.org/10.3126/on.v11i2.9536 Our Nature 2013, 11(2): 168-176